Several accountancy faculty participated in the PICPA national conference - Ledesma, Ester (Animo Repository, 1999)
Several Accountancy faculty participated in the PICPA National Conference. Master of Science in Accountancy faculty Dean Ester Ledesma was awarded the PICPA Outstanding CPA in Education while Teresita Nadurata was chosen Most Outstanding PICPA Member-Metro Manila.